2018
DOI: 10.1002/ece3.4744
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia infection can bias estimates of intralocus sexual conflict

Abstract: Males and females share most of their genome and develop many of the same traits. However, each sex frequently has different optimal values for these shared traits, creating intralocus sexual conflict. This conflict has been observed in wild and laboratory populations of insects and affects important evolutionary processes such as sexual selection, the maintenance of genetic variation, and possibly even speciation. Given the broad impacts of intralocus conflict, accurately detecting and measuring it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Thus male-biased predation indirectly selects for increased female quality. predation did not alter female fitness or male sexual-trait size.Negative intersexual correlations for fitness are an indicator of intralocus sexual conflict(Bonduriansky & Chenoweth 2009) -although this can be complicated by Wolbachia infection(Duffy et al 2019) -and we find negative correlations for fitness surrogates here -mandible size determines male fitness and LRS reflects female fitness (e.g.…”
mentioning
confidence: 61%
“…Thus male-biased predation indirectly selects for increased female quality. predation did not alter female fitness or male sexual-trait size.Negative intersexual correlations for fitness are an indicator of intralocus sexual conflict(Bonduriansky & Chenoweth 2009) -although this can be complicated by Wolbachia infection(Duffy et al 2019) -and we find negative correlations for fitness surrogates here -mandible size determines male fitness and LRS reflects female fitness (e.g.…”
mentioning
confidence: 61%
“…This asymmetry in fitness between the sexes can generate a strong negative intersexual genetic correlation for fitness, thus mimicking intra‐locus sexual conflict. In support of this prediction, experimental findings in D. simulans crosses coupled with simulations show that Wolbachia can generate signals of intra‐locus sexual conflict (Duffy et al , 2019). This possibility is currently largely overlooked as a potentially common source generating sexual conflict in arthropods, but is likely to be of genuine importance seeing the prevalence of CI‐inducing endosymbionts.…”
Section: Selfish Genetic Elements Can Generate Sexual Conflict and Sementioning
confidence: 82%
“…A negative intersexual genetic correlation for fitness is frequently interpreted as evidence for the existence of widespread intra‐locus sexual conflict where a high male fitness genotype gives rise to a low‐fitness female and vice versa . However, this negative intersexual correlation may instead be due to endosymbionts causing reproductive incompatibilities between infected males and uninfected females (Duffy et al , 2019). For example, Wolbachia (and other endosymbionts) frequently cause reproductive failure in crosses between infected males and uninfected females (CI).…”
Section: Selfish Genetic Elements Can Generate Sexual Conflict and Sementioning
confidence: 99%
“…Studies have found that 𝑟 !" may be highly sensitive to the ecological context in which genetic variation is expressed (e.g., Berger Punzalan et al 2014;Duffy et al 2019). However, our estimates of 𝑟 !"…”
Section: Quantitative Genetics Analysismentioning
confidence: 95%